Effectiveness of Endocrine Therapy in Luminal-A Breast Cancer Patients: A Literature Review - Mai, Jeremiah Nugraha; Ferdiaananda, M. Rizky; Wiradiharja, Muhammad Nur Hidayah Rayhan; Afiati, Shabrina Nur; Subangkit, Muhammad Alif Fahren (Indonesian Journal of Global Health Research, 2024)
Breast cancer ranks as one of the primary causes of mortality in women worldwide, with Southeast Asia, particularly Indonesia, witnessing a notable prevalence. Objective: To elaborate the endocrine therapy in breast cancer patients. Method: A comprehensive literature search was done across PubMed, Medline, ProQuest, Sage, and Google Scholar. Breast cancer, carcinoma mammae, luminal A, endocrine therapy, and recurrence rate, were used as the keywords. Inclusion criteria were studies on endocrine therapy in breast cancer. Initial search using title and abstract was conducted, then followed by full-text screening. Results: From 415 studies, 11 articles published between 2003 and 2022 were retrieved [RCT (n=8), clinical trial (n=1), cohort (n=1), cross-sectional (n=1)]. Endocrine therapy, also known as hormone therapy, could inhibit the growth of tumor cells by slowing down the ability of those cells to replicate. Fulvestrant and aromatase inhibitors (AI) such as anastrozole and letrozole have shown high survival and low recurrence rates. Conclusions: Adjuvant endocrine or hormonal therapy had shown remarkable outcomes for luminal A breast cancer patients, with high survival rates and very low recurrence rates. Further research was still needed to further understand the development of future treatments and to extend the research on long-term survival rates.